Financiarisation et classes sociales : introduction au dossier - Benjamin Lemoine; Quentin Ravelli (Revue de la Régulation)
By dividing wages, generalizing indebtedness and creating the illusion that ownership has become universal, financialization has changed the relationship between social groups, forms of conflict, and political representation. The purpose of this introduction, relying on empirical and sociological fieldworks, is to suggest a way to conduct researches on the consequences of financialization to class relationships. If class analysis was unavoidable in social sciences for a time, it then withered. However, since the economic crisis, the question of debt – its commodification by financial capital, as well as the forms of upward mobility, or popular over-indebtedness, that it makes possible – revives the old problem of the definition of social classes and makes it possible to understand how the relations between classes have evolved under the action of financial capital. We analyze the dynamics of construction – the work of social classification and « taxonomic surgery » – but also the social games of consolidation and destabilization of these groups. But this exercise goes with a realistic description, i.e., it also develops an analysis able to distinguish the degrees of reality taken by such groups, evaluating the asymmetries, and finally analyzing the balance of power between different social classes. While explaining the issues specific to the definition of a social class, as well as the controversies regarding their realization (or de-realization) in the social and political world, we analyze the manufacturing processes of these classes by the various operations of financialization: indebtedness, financialized savings and asset accumulation. The living conditions of populations, blurred by the massive use of credit in many countries, have largely been transformed by the financialization of the economy. This gives a temporary and fragile consistency to the political ideal – promoted by successive center-left and center-right governments – of a classless society, whose centers of gravity would be the small property and the middle-class extended to the entire social world.